Kinetic evaluation of the charge migration and H2O2 transport rates during the electrocatalytic reduction of H2O2 on thin Prussian blue films - Rešetar, Egon (Array, 2019)
Kinetic analysis of the electrocatalytic reduction of H2O2 on electrodes modified with thin Prussian blue films was performed and a full set of kinetic parameters governing the rate of the electrocatalytic reaction was determined. Rate constant (κ·k') for the catalytic reaction between H2O2 and the reduced form of Prussian blue incorporating interstitial Cs+ and K+ ions was calculated to be equal to 3.1·106 and 2.3·106 cm3·mol–1 s–1, respectively. The diffusion coefficient of H2O2 and the apparent diffusion coefficient of electrons in the reduced form of Prussian blue were found to be κ·DS(H2O2) = 2.6·10–7 cm2/s and De = 2.8·10–12 cm2/s, respectively.